Reflection on Ramadan Fasting Research Related to Sustainable Development Goal 3 (Good Health and Well-Being): A Bibliometric Analysis - AbuShihab, Katia (Journal of religion and health, 2024)
There is a large body of research on Ramadan intermittent fasting (RIF) and health in Muslim communities, that can offer insights to promote the achievement of Sustainable Development Goal 3 (SDG 3), which encompasses good health and well-being. Based on recent bibliometric evidence, we hypothesized that RIF research is highly relevant to SDG 3, particularly Targets 3.1, 3.2, 3.4, and 3.5. Therefore, this bibliometric study quantified RIF literature supporting SDG 3 and associated targets over the past seven decades and explored themes and trends. All types of research articles were extracted from the Scopus database from inception to March 2022. Microsoft Excel, Biblioshiny, and VOSviewer were used to qualitatively and quantitatively examine RIF research trends supporting SDG 3 and associated targets. We identified 1729 relevant articles. The number of publications notably increased since 1986, with a dramatic increase in 2019-2020. RIF research predominantly supported Target 3.4 (reducing risk for non-communicable diseases), with research hotspots being diabetes, diabetes medications, pregnancy, physiology, metabolic diseases, and obesity and metabolism. This target was also the most commonly supported by dedicated authors and institutions publishing on RIF, whereas other SDG 3 targets were negligibly addressed in comparison. Our comprehensive bibliometric analysis of RIF literature showed growing support for SDG 3 through positive contributions to half of the SDG 3 targets, although Target 3.4 received the most attention. We also identified knowledge gaps that may shape further research directions on RIF and promote the achievement of SDG 3 in Muslim communities.